From Workshop to Workplace: Transforming Vocational Education Through Authentic Assessment - A Systematic Review - Mumu Komaro; Amay Suherman; Bambang eko Saputro (Universitas Ahmad Dahlan, 2026)
This systematic literature review examines the evolution and effectiveness of authentic assessment practices in vocational education, with a particular focus on automotive engineering programs from 2015 to 2024. Using the PRISMA protocol, we analyzed 17 studies to identify critical success factors, challenges in implementation, and the impact of authentic assessment on both technical competencies and soft skills development. Our analysis reveals three key findings: (1) institutions that adopted comprehensive, authentic assessment frameworks achieved significant improvements in both technical competencies (35% increase) and soft skills development (28% increase); (2) successful implementation was strongly correlated with three critical factors: structured stakeholder engagement (85% effectiveness), technology integration (78% success rate), and robust quality assurance mechanisms (92% implementation rate); and (3) assessment practices evolved from basic frameworks to sophisticated, technology-integrated systems, with implementation success rates improving from 45% to 90% over the studied period. These findings provide practical guidance for vocational institutions by presenting a comprehensive framework that integrates technological innovation with pedagogical best practices while aligning closely with industry needs. The study emphasizes the importance of authentic assessment in preparing students for modern workplace demands, especially in integrating both technical and soft skills. This research advances the theoretical understanding of authentic assessment in vocational education, highlighting its role in enhancing student outcomes and fostering industry alignment.